Fruit Fly Optimization (FFO) for Solving Economic Dispatch Problem in Power System - Harold, Geruna; Nor Rul Hasma, Abdullah; Maulana Zulfikar, Asril; Mahfuzah, Mustafa; Rosdiyana, Samad; Pebrianti, Dwi (2017)
One of the main issues that still emerging as the most complex fundamental problems in power system operation is Economic dispatch (ED). This paper presents the application of Fruit Fly Optimization (FFO) algorithm technique for solving ED problem. The FFO algorithm is applied to minimize the cost of generating units by allocating the most optimum value of real power for a specific generating unit in a power system while operated within the limitation. The effectiveness of the proposed technique was validated on standard IEEE-26 bus Reliability Test System (RTS).